Pelatihan Perencanaan Pembelajaran Berbasis Deep Learning untuk Meningkatkan Kompetensi Guru Sekolah Muhammadiyah : Pengabdian - Mujianto, Gigit; Widodo, Rohmad; Agustinus, Agustinus; Setiawan, Arif (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
The challenges of 21st-century education require teachers to design meaningful learning that is oriented towards students' in-depth understanding. However, learning plans in the field are often still viewed as administrative documents, thus not optimally supporting deep learning-based learning. This community service activity aims to test the effectiveness of deep learning-based learning planning training in improving the competency of Muhammadiyah School teachers. The method used was quantitative with a one-group pretest–posttest design for 30 Muhammadiyah junior high school teachers in Malang Regency. Data were obtained through pre- and post-training tests, supported by interviews, observations, and documentation, then analyzed descriptively using score comparisons and N-gain values. The results showed a significant increase in teacher competency in the moderate to high category, confirming that this training is effective in improving teacher competency and encouraging a paradigm shift in learning planning as the basis for meaningful learning.